Laser Produced Hydrophilic and Hydrophobic Silicon Surfaces - Hatem, A. A.; Rasheed, B. G.; Ahmed, Naser M. (Al-Nahrain Journal for Engineering Sciences, 2024)
Two lasers were utilized for silicon processing using photoelectrochemical etching and laser texturing in order to produce nano/micro structures, respectively. Photoelectrochemical etching process utilizes a CW diode laser of 532 nm wavelength was used to support electrochemical etching for both n-type and p-type conductivity. While laser texturing process was employed using pulsed fiber laser of 1064 nm wavelength. Various characterization methods were devoted to examine silicon micro/nanostructures surfaces produced by lasers. These methods include AFM, SEM and Raman scattering to provide clear evidence about formation of micro/nanostructures abundant at silicon surfaces.  Moreover, FTIR analysis for the laser produced silicon surfaces could emphasize whether the resultant silicon surface is hydrophilic or hydrophobic. Image analysis software adopted a side view micro image was used to measure the contact angle between the water droplet and silicon micro/nano-surfaces. It is found that the laser produced silicon nanostructure by photoelectrochemical etching creates a hydrophobic surface and even super hydrophobic with contact angle of 130 degrees for 50 nm average size. In addition, utilizing fiber laser of high repetition rate for laser texturing produces microstructures that are super hydrophilic with contact angle could reach 8 degrees for a surface dimension of 50 μm.